Preference Intensities in Repeated Collective Decision-Making - Moritz Drexl; Andreas Kleiner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We study decision rules for committees that repeatedly take a binary decision. Committee members are privately informed about their payoffs and monetary transfers are not feasible. In static environments, the only strategy-proof mechanisms are voting rules which are criticized for being inefficient as they do not condition on preference intensities. The dynamic structure of repeated decision-making allows for richer decision rules that overcome this inefficiency by making use of information on preference intensities. Nonetheless, we show that often simple voting is optimal for two-person committees. This holds for many prior type distributions and irrespective of the agents' patience.
Keywords: D72; D82; C61; 330